The Effect of Blanching Time and Sodium Metabisulfite Concentration on The Characteristics of Banana Flour (Musa paradisiaca) - Marina Arta Rahayu; Lukman Hudi (Universitas Muhammadiyah Sidoarjo, 2021)
The aim of this research was to determine effect of blanching time and sodium metabisulfit concentration on the characteristics banana flour. This research was conducted in Product Development Laboratory of University Muhammadiyah Sidoarjo from February to April 2019 used randomized block design. The first treatment was blanching time L1 (0 minute), L2 (5 minutes), L3 (10 minutes) and second treatment was sodium metabisulfit concentration B1 (0 ppm), B2 (300 ppm), B3 (600 ppm). The data obtained were then analyzed using analysis of variance (ANOVA) and further test least significant diference 5%. The result indicated that there was no interaction between the blanching time and concentration of sodium metabisulfit. Organoleptic test showed significant differences in the color and texture of banana flour. The concentration of sodium metabisulfit affected the lightness and yellowness value of banana flour. The best treatment was blancing time 5 minutes and sodium metabisulfit concentration 600 ppm (L2B3) showed that moisture of 8,46%, ash content of 2,54%, yield of 34,83%, density of 0,67 g/ml, lightness 88,94, redness 2,85, yellowness 8,91, reduced sugar of 0,28 mg/ml and organoleptic test of texture 4,95, color 4,00, and aroma 3,95.